MENGGALI POTENSI TRANSFORMASI DIGITAL: PENERAPAN ARTIFICIAL INTELLIGENCE (AI) DALAM PENULISAN ARTIKEL ILMIAH PADA MAHASISWA PSDKU UNTAD MOROWALI - Hilmansyah, Teguh; Farid, Erwan Sastrawan; Hardani, Ririen; Amin, Mohammad (Jurnal Abdimas Bina Bangsa, 2024)
This community service aims to enhance the scientific writing skills of PSDKU UNTAD Morowali students through the utilization of artificial intelligence (AI), recognizing the importance of writing skills for academic and societal contributions. The action research method was employed, involving students in problem identification, planning, and evaluation. The training was conducted in four sessions, covering AI introduction, reference selection, outline drafting, and grammar and plagiarism checks. The evaluation showed an improvement in understanding, with an average score of 4.15, where 83.75% of participants demonstrated a good grasp of the material. This program successfully met the students' needs, accelerated the writing process, and boosted their confidence through hands-on practice. Further development is needed for advanced training and online modules. These results underscore the importance of AI in improving the quality of students' scientific writing